The parameters for writing Muslim Filipino literary history - Asain, Calbi A. (2003)
The Muslim cultural communities in our country consist of thirteen ethno-linguistic groups found mostly in Mindanao. These are the Badjao, Iranon, lama Mapun, Ka 'agan, Kalibugan, Maguindanaon, Maranao, Molbog, Palawani, Sama, Sangir, Tausug, and Yakan. Each of these cultural communities has its own literature, the history of which has yet to be traced and written systematically. This paper explores the possible parameters for writing the literary history of Muslim Filipinos as an integral component of the Filipino literary history by addressing related issues and concerns. Hopefully, this will contribute something to the writing or rewriting of the Filipino literary history, which should reflect the diverse nature of our national literary heritage.
Includes bibliographical references (pages 67-68).